AB0636 Alteration of vitamin d after a whole body uv-b exposure in context of a diet. (23rd January 2014) - Majer, M.; Biersack, M.; Piazena, H.; Braun, T.; Höhne-Zimmer, V.; Burmester, G.-R.; Buttgereit, F.; Uebelhack, R.; Detert, J.
Abstract : Background: In the European population of northern climes poses the deficiency of vitamin D (vitD) a frequent problem, especially in autumn and winter 1, 2 . On the other hand it is difficult to supply a necessary dose of vitD in a diet 1 . The substitution in case of deficiency of vitD occurs principally orally 3 . Objectives: The aim of this pilot project was to investigate, if 1) an UV-B-stimulus and 2) a diet rich in vitD have an influence on vitD level in autumn and winter months. Methods: 20 healthy female subjects (age: 21-25 years, UV skin types: I - III ) received 3 whole body irradiation with an solar simulated UV-B-stimulus on 3, not successive days, within one week in winter 2011/2012. The dose of the UV-B-stimulus came to 40%, 60% and 75% of the minimal erythema dose (MED) according to UV skin type classification. The level of vitD-metabolites, 25-hydroxy-vitD (25-OH-vitD) and 1.25-Dihydroxy-vitD (1.25-diOH-vitD) were measured on day (d) 1, 8, 36 and 50 (before the irradiation, 3 d, 4 and 6 weeks after the irradiation). A questionnaire including food examples rich of vitD has been enquired on d1. Results: The level of both vitD-metabolites increased significantly on d8 (25-OH-vitD - p<0, 001 and 1.25-diOH-vitD – p=0, 009). On d36 and d50 the level of 25-OH-vitD was also higher than baseline level ( p < 0, 001 on d36, p = 0, 043 on d50). There was no correlation between a diet rich in vitD and the beginning level of 25-OH-vitD (k=0, 17). Conclusions: Calculated whole body UV-B-irradiation resulted in a significant and long-lasting increase of the level of vitD. A correlation between a diet rich in vitD and the beginning level of 25-OH-vitD couldn't be shown. It is necessary to investigate if UV-B-stimulus could be used as an alternative to an oral substitution in case of deficiency of vitD. References: Referenzwerte für die Nährstoffzufuhr. Vitamin D. Deutsche Gesellschaft für Ernährung (DGE), 1. Auflage, 4. korrigierter Nachdruck 2012 Webb AR, Engelsen O, Calculated ultraviolet exposure levels for a healthy vitamin D status. Photochem Photobiol, 2006;821:697-703 Chandra P, Wolfenden LL, Ziegler TR et al Treatment of vitamin D deficiency with UV light in patients with malabsorption syndromes: a case series. Photodermatol Photoimmunol Photomed 2007;5:179-185 Disclosure of Interest: None Declared